NEW EFFECTIVE STRUCTURAL SCHEME AND PRINCIPLE OF OPERATION PARAMETERS FOR YARN STRETCHING TOOL OF RING SPINNING MACHINE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The paper written about a new effective design scheme and the principle of operation of a machine for stretching yarn of a ring-spinning device based on the parameters of belt bushings. The mathematical model and the results of solving the problem of oscillations of the axis of the composite squeezing roller of the drawing apparatus of the spinning machine have been determined. The recommended values of the roller parameters are given. Based on the analysis of the research results and the conditions for obtaining high-quality yarn, the recommended parameter values for each squeezing rollers were determined.